2016
DOI: 10.1111/jop.12443
|View full text |Cite
|
Sign up to set email alerts
|

BRAFV600E mutation in the diagnosis of unicystic ameloblastoma

Abstract: The BRAFV600E antibody (clone VE1) IHC may show non-specific staining, but molecular assays may be useful for the diagnosis of unicystic ameloblastoma, in conjunction with clinical, radiological and histopathological features.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
65
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(76 citation statements)
references
References 26 publications
9
65
0
2
Order By: Relevance
“…In our data, four of BRAF IHC‐positive/ BRAF V600E+ cases that had no BRAF mutation were seen. False‐positive results from the assessment of BRAF mutations by IHC using the VE1 antibody were previously reported 23 . The reason for this remains unclear, but could be caused by a sampling problem.…”
Section: Discussionmentioning
confidence: 99%
“…In our data, four of BRAF IHC‐positive/ BRAF V600E+ cases that had no BRAF mutation were seen. False‐positive results from the assessment of BRAF mutations by IHC using the VE1 antibody were previously reported 23 . The reason for this remains unclear, but could be caused by a sampling problem.…”
Section: Discussionmentioning
confidence: 99%
“…These studies reported the identification of highly recurrent somatic, activating mutations in the signaling pathways of the mitogen-activated protein kinase (MAPK) and Hedgehog in ameloblastoma. The interest in these two pathways was stirred as they are known to be active during tooth development [12][13][14] and more specifically, mutations in MAPK components (i.e., BRAF, KRAS and FGFR2) have been identified in both benign [15] and malignant tumors [16][17][18] In 2015, an additional investigation regarding BRAF and Hedgehog related-SMO mutations was published, which examined not only ameloblastomas (ameloblastoma and unicystic ameloblastoma), but also a series of odontogenic carcinomas [19].…”
Section: Ameloblastomamentioning
confidence: 99%
“…The mutation status of BRAF has been examined in a small number of unicystic ameloblastomas (n = 15) [11,15,19] and that of SMO in even a smaller number (n = 7) [19]. In total, 73% of the examined unicystic ameloblastomas (all located in the mandible) were found to bear the BRAFV600E mutation, however none of them showed mutations in SMO.…”
Section: Ameloblastomamentioning
confidence: 99%
“…However, COC, one of the entities requiring differential diagnosis with ameloblastomas, had a high probability for CTNNB1 mutation, but was consistently negative for BRAF V600E mutation (Ahn et al, ; de Sousa, Moreira, Gomez, & Gomes, ; Yukimori et al, ). Because of this, some researchers suggested that the BRAF V600E mutation might have diagnostic implications (Brown et al, ; Pereira et al, ). We noticed that the BRAF V600E mutation rate in the current cohort (3/5, 60.0%) was higher than other less common cell type of ameloblastoma, including acanthomatous (44%, 7/16), granular (50%, 2/4), and basaloid (33%, 2/6).…”
Section: Discussionmentioning
confidence: 99%
“…The most common mutation identified is BRAF V600E , while others include FGFR2 , KRAS , NRAS, and HRAS . It is suggested that 46% to 82% of solid/multicystic ameloblastomas harbors BRAF V600E mutation (Brown et al, ; Guan et al, ; Kurppa et al, ; Sweeney et al, ), while UAM demonstrated higher BRAF V600E mutation frequency (63%–94%) (Heikinheimo et al, ; Pereira et al, ). More recent studies revealed that less common cell types of ameloblastoma showed different rates of BRAF V600E mutation: acanthomatous (44%, 7/16), granular (50%, 2/4), and basaloid (33%, 2/6) (Gultekin et al, ; You et al, ).…”
Section: Introductionmentioning
confidence: 99%